Removing of methylene blue dye from it aqueous solutions by using cement kiln dust(ckd) - Hazim. A.H.Al Robai; Khalid. S.Ali (Al-Qadisiyah Journal of Pure Science, 2018)
In this study, the efficiency of the use of cement kilns dust (CKD investigated to remove the methylene blue dye (MB) from its aqueous solutions, in order to achieve it, a series of adsorption experiments conducted in lab for equilibrium reactions to test the effect of important parameters, the dose of adsorbent (CKD) , concentration of the adsorbate (methylene blue dye) , pH value and contact  time.The results of adsorption experiments of the equilibrium reactions showed that, it is clear the removal of the dye from its aqueous solutions was relatively low at acidic conditions may be due to the presence of an abundance of hydrogen ions H + gained from hydrochloric acid. An increase the value of pH to 7.5 and 9.5 have been observed a significant increase in the rate of removal of dye. It may be due to the basic conditions that lead to an abundance of hydroxyl ions (OH-).